Trả lời:
![verified](https://1900.edu.vn/images/exam/verified.webp)
Ta có: Δy=f(x+Δx)−f(x)=cos(x+Δx)−cosx=−2sin(x+Δx2).sinΔx2
ΔyΔx=−2sin(x+Δx2).sinΔx2Δx=−sin(x+Δx2).sinΔx2Δx2
limΔx→0ΔyΔx=limΔx→0−sin(x+Δx2).sinΔx2Δx2=−sinx.
Vậy f'
Ta có: Δy=f(x+Δx)−f(x)=cos(x+Δx)−cosx=−2sin(x+Δx2).sinΔx2
ΔyΔx=−2sin(x+Δx2).sinΔx2Δx=−sin(x+Δx2).sinΔx2Δx2
limΔx→0ΔyΔx=limΔx→0−sin(x+Δx2).sinΔx2Δx2=−sinx.
Vậy f'
CÂU HỎI HOT CÙNG CHỦ ĐỀ
Câu 1:
Chứng minh rằng hàm số không có đạo hàm tại nhưng có đạo
hàm tại .
Chứng minh rằng hàm số không có đạo hàm tại nhưng có đạo
hàm tại .
Xem đáp án »
03/04/2024
114